Influence of Interspecies Transmission of Atypical Bovine Spongiform Encephalopathy Prions to Hamsters on Prion Characteristics - Miyazawa, Kohtaro; Masujin, Kentaro; Matsuura, Yuichi; Iwamaru, Yoshifumi; Okada, Hiroyuki (Frontiers in Veterinary Science, 2020)
Bovine spongiform encephalopathy (BSE) is a prion disease in cattle, is classified into the classical type (C-BSE) and two atypical BSEs, designated as high-type (H-BSE) and low-type (L-BSE). These classifications are based on the electrophoretic migration of the proteinase K resistant core (PrPres) of the disease-associated form of the prion protein (PrPd). In a previous study, we succeeded in transmitting the H-BSE prion from cattle to TgHaNSE mice overexpressing normal hamster cellular PrP (PrPC). Further, western blot analysis demonstrated that PrPres banding patterns of the H-BSE prion were indistinguishable from those of the C-BSE prion in TgHaNSE mice. In addition, similar PrPres glycoprofiles were detected among H-, C-, and L-BSE prions in TgHaNSE mice. Therefore, to better understand atypical BSE prions after interspecies transmission, H-BSE prion transmission from TgHaNSE mice to hamsters was investigated, and the characteristics of classical and atypical BSE prions among hamsters, wild-type mice, and mice overexpressing bovine PrPC (TgBoPrP) were compared in this study using biochemical and neuropathological methods. Identical PrPres banding patterns were confirmed between TgHaNSE mice and hamsters in the case of all three BSE prion strains. However, these PrPres banding patterns differed from those of TgBoPrP and wild-type mice infected with the H-BSE prion. In addition, glycoprofiles of TgHaNSE mice and hamsters infected with the L-BSE prion differed from those of TgBoPrP mice infected with the L-BSE prion. These data indicate that the PrPC amino acid sequences of new host species rather than other host environmental factors may affect some molecular aspects of atypical BSE prions. Although three BSE prion strains were distinguishable based on the neuropathological features in hamsters, interspecies transmission modified some molecular properties of atypical BSE prions, and these properties were indistinguishable from those of C-BSE prions in hamsters. Taken together, PrPres banding patterns and glycoprofiles are considered to be key factors for BSE strain typing. However, this study also revealed that interspecies transmission could sometimes influence these characteristics.